Business accountability in corporate social responsibility: case studies of a multinational corporation and a government linked company / Fathilatul Zakimi Abdul Hamid - Abdul Hamid, Fathilatul Zakimi (Institute of Graduate Studies, UiTM, 2018)
Numerous studies have investigated corporate social responsibility (CSR) towards stakeholders, but little is known concerning the process of how corporations are accountable in their CSR initiatives. This study posits that accountability is an integral part of the business strategy. Hence, the study aims to gain a deeper understanding of corporate accountability from the perspective of CSR initiatives in Malaysia. As such, the research addressed three aims: i) to conceptualise the meaning of accountability; ii) to provide insightful understanding of institutionalised corporate accountability mechanisms; iii) to theorising the concept from a CSR business initiatives perspective. Qualitative research methodology was employed appropriate for eliciting the process of accountability from the CSR perspective. Specifically, this study comprised a multiple case study for which two telecommunications companies were selected. The telecommunications industry contributes to the country’s economic development and has a different shareholding structure from other firms…